Anti-creep laser fusion flange bottom disc and preparation method thereof

CN122625664BActive Publication Date: 2026-10-23BAOMEITE (SHANGHAI) INTELLIGENT ENG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611122225.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-23
Estimated Expiration
2046-07-28

AI Technical Summary

Technical Problem

然而,该依赖铼元素的制备方法存在缺陷

Benefits of technology

本发明提供的抗蠕变激光熔融法兰底盘的制备方法,在无铼添加的前提下,将铌元素与硅元素在激光熔融过程中的偏析缺陷逆向调控为有益强化;在第二阶段激光熔融中控制体能量密度与冷却速率,使铌元素发生偏析系数大于1的正向偏析并被截留于枝晶干核心,原位析出NbC碳化物纳米颗粒,形成高强度主干枝晶骨架;同时使硅元素发生偏析系数小于1的负向偏析并富集于枝晶间区域,与铪、铌等元素共晶生成热力学稳定的高熔点硅化物,构建高韧性枝晶间网络;解决了传统认知中铌、硅添加必然导致成分不均与热裂纹的技术偏见,使无铼高铬合金在1200℃高温重载下的稳态蠕变速率得到显著抑制。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122625664B_ABST
    Figure CN122625664B_ABST
Patent Text Reader

Abstract

The application discloses an anti-creep laser melting flange bottom disc and a preparation method, relates to the green manufacturing category, and belongs to the plating technical field of metal materials, and comprises the following steps: constructing a thermodynamic initial field by pretreating a base body; preparing modified alloy powder based on IN738LC and adding niobium, silicon, hafnium and carbon; forming a transition layer containing in-situ generated NbN nanoparticles and a self-healing liquid film network under a trace oxygen-nitrogen atmosphere by first-stage laser melting; inducing positive segregation of the niobium element to strengthen the dendrite stem and negative segregation of the silicon element to strengthen the interdendrite by controlling the bulk energy density and the cooling rate in the second-stage laser melting, so as to construct an anti-creep main structure; and finally, the brittle sigma phase and the Laves phase are respectively converted into nanoscale grain boundary pinning phases and spherical dislocation pinning phases through hot isostatic pressing, directional recrystallization and double-stage aging treatment; and the application realizes long-term stable operation of the rhenium-free high-chromium alloy at 1200 DEG C, and reduces the manufacturing cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal plating technology, to the scope of green manufacturing, and particularly to an anti-creep laser melting flange chassis and its preparation method. Background Technology

[0002] In modern metallurgy and special steel processing, high-temperature annealing is a core process affecting the final mechanical properties and microstructure of steel coils. As a core load-bearing component inside the high-temperature annealing furnace, the flange base operates under harsh conditions. In the special steel coil annealing process, the flange base must bear the weight of steel coils weighing up to 20 tons for extended periods at temperatures exceeding 1200℃. Under the combined effects of high temperature and constant stress, the flange base material undergoes creep. Creep refers to the physical process in which the amount of plastic deformation of a solid material slowly increases over time when subjected to constant stress. For metallic materials, the creep mechanism is fully activated when the service temperature exceeds 30% to 50% of its absolute melting point. A temperature of 1200℃ is close to or even exceeds the melting point of most commercially available metallic materials, placing them in a region of significant creep acceleration. At this temperature, vacancy diffusion within the material intensifies, relative slip occurs at grain boundaries, and the rate at which dislocations climb over barriers increases exponentially, ultimately leading to the initiation of microscopic voids and cracks within the material, and subsequently, creep fracture.

[0003] Therefore, developing a creep-resistant flange chassis manufacturing technology capable of long-term stable operation at 1200℃ and under high stress conditions has become a core industrial bottleneck that needs to be overcome in the current high-end equipment manufacturing field. Meanwhile, based on the development concept of green manufacturing, the material selection and process design of this flange chassis reflect the energy-saving and high-efficiency characteristics of green manufacturing and meet the industrial needs of new energy applications and energy conservation and emission reduction.

[0004] Existing technologies for preparing high-temperature creep-resistant materials mainly focus on the development of nickel-based single-crystal or directionally solidified high-temperature alloys, such as CM247LC, SD247, and ABD-900AM alloy systems for additive manufacturing. The mainstream process route of these existing technologies involves adding a large amount of the scarce rhenium element, with a mass fraction of 3.0% to 4.0%, supplemented by refractory metals such as tantalum and tungsten. The extremely low diffusion rate of rhenium in the γ matrix stabilizes the γ′ strengthening phase, thereby achieving creep resistance above 1200℃. However, this rhenium-dependent preparation method has drawbacks. First, rhenium is a scarce metal on Earth and has a high price, leading to high manufacturing costs for flange chassis and limiting its large-scale industrial application. Second, existing advanced alloys require low chromium content to accommodate large amounts of refractory elements and suppress the precipitation of harmful topologically close-packed phases, directly resulting in a significant decrease in the material's resistance to high-temperature oxidation and hot corrosion at 1200℃. Summary of the Invention

[0005] This invention overcomes the shortcomings of the prior art and provides an anti-creep laser melting flange chassis and its preparation method.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is: a method for preparing an anti-creep laser melting flange chassis, comprising: S1. Prepare the flange base plate and perform pretreatment and construction of the initial thermodynamic field; S2. Prepare modified alloy powder, wherein the modified alloy powder is based on IN738LC alloy and contains niobium, silicon, hafnium and carbon elements; S3. Based on the established thermodynamic initial field, modified alloy powder is used to perform the first stage laser melting on the surface of the flange chassis substrate to induce in-situ chemical reaction in order to form a transition layer and precursor. S4. Based on the precursor, modified alloy powder is used to perform a second-stage laser melting of the flange chassis substrate, and an anti-creep main structure is constructed by inducing reverse segregation. S5. Post-process the flange chassis by transforming the brittle phase at the microscopic grain boundaries into a strengthening phase with dislocation pinning effect through multi-stage thermodynamic reconstruction to obtain the final product.

[0007] In a preferred embodiment of the present invention, the pretreatment in step S1 includes: placing the substrate in a controlled atmosphere heat treatment furnace for high-temperature solution treatment and then cooling it; using alumina particles with a particle size of 50~100μm to perform high-pressure airflow sandblasting on the surface of the cooled substrate to roughen its surface; fixing the sandblasted substrate on a constant temperature heating platform and preheating it at 400~450℃ for 10-12h to construct a uniformly distributed thermodynamic initial field.

[0008] In a preferred embodiment of the present invention, the modified alloy powder uses IN738LC high-temperature alloy as the matrix and adds niobium, silicon, hafnium and carbon elements; the chemical composition of the modified alloy powder in the following mass percentage range is: chromium 15.5%~16.4%, cobalt 8.0%~9.0%, molybdenum 2.5%~3.5%, tungsten 3.0%~4.0%, aluminum 4.5%~5.2%, titanium 2.4%~3.7%, tantalum 3.0%~4.0%, niobium 1.5%~2.5%, silicon 0.3%~0.6%, hafnium 0.1%~0.3%, carbon 0.12%~0.18%, boron 0.01%~0.02%, zirconium 0.02%~0.08%, with the remainder being nickel matrix and unavoidable trace impurities.

[0009] In a preferred embodiment of the present invention, step S2, the preparation of modified alloy powder includes: weighing raw materials according to chemical composition, melting them in an induction melting furnace at 1500~1600℃ and electromagnetically stirring to make the elements diffuse uniformly; using high-pressure nitrogen to atomize the melt, forming spherical particles, and then sieving to obtain modified alloy powder with a particle size of 15μm~53μm.

[0010] In a preferred embodiment of the present invention, the first stage of laser melting in step S3 is carried out in a protective atmosphere containing oxygen and nitrogen, wherein the volume fraction of oxygen is 50~150ppm and the volume fraction of nitrogen is 50~100ppm, so as to induce the in-situ generation of NbN nanoparticles and self-healing liquid film network.

[0011] In a preferred embodiment of the present invention, the reverse segregation control in step S4 is as follows: niobium, which has a positive segregation tendency, is enriched in the core of the primary dendrite trunk to form a niobium-reinforced dendrite trunk; silicon, which has a negative segregation tendency, is selectively enriched in the interdendritic region, reacting with elements such as hafnium and niobium to generate high-melting-point silicides, thereby forming silicon-reinforced interdendritic regions; the second stage laser melting employs a spiral scanning superimposed layer 90° rotation, with a laser volume energy density of 55~75 J / mm³ and a cooling rate of 10... 4 ~10 5 K / s, to trigger positive segregation of niobium with a segregation coefficient of 1.5~2.0 and negative segregation of silicon with a segregation coefficient of 0.5~0.7.

[0012] In a preferred embodiment of the present invention, in step S5, the post-processing includes sequential hot isostatic pressing, directional recrystallization, and two-stage aging. The hot isostatic pressing is used to close microscopic defects and promote the homogenization and diffusion of alloying elements. The directional recrystallization is used to induce preferential grain growth along a specific direction by applying a directional dynamic temperature gradient flow field to reduce transverse weak grain boundaries. The two-stage aging is used to induce the transformation of the σ-brittle phase into a nanoscale grain boundary pinning phase and the spheroidization of the Laves phase into a dislocation pinning phase by holding the phase at different temperatures in stages.

[0013] In a preferred embodiment of the present invention, the two-stage aging treatment includes: a first stage of isothermal holding at 1120°C for 4-6 hours to induce the σ phase to transform into a discontinuous nano-reinforced phase with a size of 50-200 nm; and a second stage of isothermal holding at 850°C for 10-15 hours to induce the Laves phase to spheroidize into a (Ni,Co,Hf)2(Nb,Si) type dislocation pinning phase.

[0014] In a preferred embodiment of the present invention, in step S4, laser-induced reverse segregation is used to make the positive segregation degree of niobium element greater than the negative segregation degree of silicon element, so that NbC carbide strengthening phase is formed in the dendrite trunk and high melting point silicide strengthening phase is formed between dendrites.

[0015] This invention provides a creep-resistant laser melting flange chassis, comprising: Flange base plate; The transition layer is metallurgically bonded to the substrate surface. It contains NbN nanoparticles and has a self-healing liquid film network between the dendrites, which is pinned by nanocomposite oxides and HfNb2. The functional main layer, stacked on the transition layer, has NbC carbides formed by the positive segregation of niobium to strengthen the dendrite trunk; and high-melting-point silicides formed by the negative segregation of silicon to strengthen the interdendritic structure. The niobium-strengthened dendrite trunk and the silicon-strengthened interdendritic structure together constitute the reverse segregation structure. The functional host layer has a discontinuous distribution of nano-σ-reinforcing phase and spherical (Ni,Co,Hf)2(Nb,Si) type Laves dislocation pinning phase at the grain boundaries; In high-temperature service environments, three oxide films are generated in situ on the outer surface of the functional main body layer. The oxide films, from the inside to the outside, are: an amorphous SiO2 inner oxide layer, a Cr2O3 main protective layer, and a Nb2O5-SiO2 composite self-healing layer.

[0016] This invention addresses the shortcomings of the prior art and has the following beneficial effects: The method for preparing an anti-creep laser melting flange chassis provided by this invention reverses the segregation defects of niobium and silicon elements during the laser melting process into beneficial strengthening, without the addition of rhenium. In the second stage of laser melting, the bulk energy density and cooling rate are controlled to cause niobium to undergo positive segregation with a segregation coefficient greater than 1 and be trapped in the dendrite trunk core, precipitating NbC carbide nanoparticles in situ to form a high-strength main dendritic framework. At the same time, silicon is caused to undergo negative segregation with a segregation coefficient less than 1 and be enriched in the interdendritic region, co-crystallizing with elements such as hafnium and niobium to form thermodynamically stable high-melting-point silicides, constructing a high-toughness interdendritic network. This method solves the technical prejudice that the addition of niobium and silicon inevitably leads to compositional inhomogeneity and hot cracking, and significantly suppresses the steady-state creep rate of rhenium-free high-chromium alloys under high temperature and heavy load at 1200℃.

[0017] This invention utilizes a multi-stage thermodynamic post-processing technique to transform the brittle σ-phase and Laves phase, which are easily precipitated in high-chromium alloy systems, into nanoscale grain boundary pinning points and spherical dislocation pinning phases. Hot isostatic pressing (HIP) induces localized dissolution of the coarse, irregular, brittle phases; directional recrystallization reduces the number of weak transverse grain boundaries; and a two-stage aging process controls the phase transformation dynamics. This allows the σ-phase to evolve in situ into discontinuously distributed 50-200 nm nanoscale strengthening particles, and the Laves phase to topologically transform into rounded (Ni,Co,Hf)₂(Nb,Si) type spherical clusters. This defect transformation strategy changes the traditional metallurgical understanding that high-chromium, niobium, and silicon combinations inevitably lead to matrix embrittlement. It transforms the harmful phases that would otherwise disrupt matrix continuity into strengthening units capable of pinning grain boundary slip and hindering dislocation movement, thereby improving the creep fatigue life and structural integrity of the flange chassis under ultra-high temperature conditions of 1200℃.

[0018] This invention introduces a trace oxygen-nitrogen mixed protective atmosphere during the laser melting transition layer stage, combined with the addition of hafnium, to construct a self-healing liquid film network and a nano-reinforcing phase. At the end of the transient molten pool solidification, trace oxygen reacts with niobium and silicon enriched in the dendrites to generate nanoscale composite oxides. Simultaneously, hafnium and niobium eutectic form a high-melting-point HfNb2 compound. The three-dimensional support framework constructed by both enhances the surface tension and tensile stress resistance of the interdendritic liquid film, and achieves dynamic backfilling of cracks in the liquid metal through capillary pumping effect, effectively suppressing the initiation and propagation of hot cracks. Simultaneously, nitrogen in-situ generates dispersed NbN nano-ceramic particles in the molten pool, acting as heterogeneous nucleation cores to promote grain refinement and block the growth of coarse columnar crystals. The synergistic effect of the above-mentioned in-situ physicochemical reactions enables the high-chromium alloy of this invention to obtain a high-density, crack-free transition layer and precursor during laser additive manufacturing.

[0019] This invention leverages the inherent advantages of the high chromium and high molybdenum content of the IN738LC base alloy, and utilizes the synergistic effect of conventional elements such as niobium, silicon, hafnium, and carbon to achieve a synergistic improvement in the material's resistance to high-temperature oxidation, hot corrosion, and creep. Under high-temperature service conditions, silicon, chromium, and niobium elements in the alloy matrix undergo selective outward diffusion, forming a three-layer composite oxide film in situ: an amorphous SiO2 inner oxide layer, a dense Cr2O3 main protective layer, and a Nb2O5-SiO2 composite outer layer with high-temperature flow self-healing capabilities. This effectively blocks the inward diffusion channels of oxygen atoms. Simultaneously, the high molybdenum content retained in the matrix provides solid solution strengthening through lattice distortion, further enhancing the material's yield strength at extreme high temperatures. This significantly reduces material costs and enables long-term stable operation under 1200℃ high-temperature heavy-load annealing scenarios, aligning with the industrial development direction of green manufacturing and energy conservation. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Figure 1 This is a flowchart of a preferred embodiment of the present invention. Detailed Implementation

[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0023] Application Overview: The flange chassis of this invention operates in a high-temperature annealing environment at 1200℃, bearing a 20-ton steel coil. The flange chassis must withstand constant mechanical stress and resist atomic diffusion, grain boundary slip, oxidation, and hot corrosion caused by the 1200℃ temperature. The current mainstream technology in the industry uses rhenium-containing nickel-based superalloys, such as CM247LC and ABD-900AM, combined with laser additive manufacturing technology. However, this approach has the following drawbacks: First, rhenium is expensive, causing the manufacturing cost of large flange chassis to exceed the acceptable range for industrialization; second, to ensure the structural stability of the rhenium-containing alloy, the chromium content needs to be reduced, which degrades the material's oxidation and hot corrosion resistance at 1200℃, and the peeling of the oxide scale accelerates the initiation of creep cracks.

[0024] Although IN738LC alloy possesses good corrosion resistance potential and cost advantages due to its high chromium content (15.5%~16.4% by mass) and high molybdenum content (1.5%~2.5% by mass), existing technologies have encountered technical obstacles when attempting to apply it to 1200℃ environments. The current technical problem to be solved in the industry is: how to break through the technical limit of IN738LC alloy's maximum service temperature of no more than 900℃ without adding rhenium, while simultaneously solving the problems of hot cracking and brittle phase precipitation that are prone to occur in high chromium alloys during laser melting.

[0025] The reason why existing technologies cannot solve the above problems lies in the limited understanding of element segregation and brittle phases in traditional metallurgy. This understanding leads to a technological bias, believing that adding niobium and silicon to IN738LC to improve high-temperature strength will cause three uncontrollable defects. First, segregation defects: Niobium and silicon have a melting point difference of 1063℃. During the rapid solidification process of the laser molten pool, niobium tends to be enriched in the dendritic trunk region, while silicon tends to be enriched in the interdendritic region, resulting in compositional inhomogeneity. Second, brittle phase precipitation defects: The combination of high chromium, niobium, and silicon will precipitate brittle σ phase and Laves phase at the grain boundaries in the thermal cycling range of 500℃~900℃, affecting the continuity of the matrix. Third, hot cracking defects: The segregation of niobium and silicon widens the solidification temperature range of the alloy to 150℃~200℃. At the end of solidification, a low-melting-point liquid film forms between the dendrites. Under the action of solidification shrinkage stress, the liquid film tears to form a through-thickness hot crack. Based on the aforementioned biases, the industry believes that the IN738LC alloy is not capable of long-term stable service at 1200℃, and attempts to modify it by adding niobium and silicon are likely to lead to cracking.

[0026] Optimizing a single laser power or scanning speed, or adding nanoparticles using conventional mechanical alloying methods, cannot alter the aforementioned thermodynamic and kinetic evolution laws. Conventional techniques suppress segregation and brittle phases by reducing the degree of alloying, but this leads to a decrease in high-temperature strength, making it difficult to exceed the 1200℃ service limit.

[0027] This invention addresses the creep and cracking problems of rhenium-free high-chromium alloys at 1200℃ by constructing a differentiated end-process technology and proposing reverse segregation engineering and defect transformation strategies. Specifically, this invention uses laser dynamics to regulate niobium and silicon segregation into beneficial segregation, enabling niobium to strengthen dendrite trunks and silicon to strengthen interdendritic spaces; multi-stage thermodynamic post-treatment transforms the σ phase and Laves phase into nanoscale grain boundary pinning points; and by introducing trace amounts of hafnium and controlling the oxygen content of the atmosphere, a self-healing liquid film network is constructed in situ.

[0028] Exemplary method: like Figure 1 As shown, a method for fabricating a creep-resistant laser melting flange chassis includes: S1. Prepare the flange base plate and perform pretreatment and construction of the initial thermodynamic field; S2. Prepare modified alloy powder, wherein the modified alloy powder is based on IN738LC alloy and contains niobium, silicon, hafnium and carbon elements; S3. Based on the established thermodynamic initial field, modified alloy powder is used to perform the first stage laser melting on the surface of the flange chassis substrate to induce in-situ chemical reaction in order to form a transition layer and precursor. S4. Based on the precursor, modified alloy powder is used to perform a second-stage laser melting of the flange chassis substrate, and an anti-creep main structure is constructed by inducing reverse segregation. S5. Post-process the flange chassis by transforming the brittle phase at the microscopic grain boundaries into a strengthening phase with dislocation pinning effect through multi-stage thermodynamic reconstruction to obtain the final product.

[0029] In high-energy-beam laser additive manufacturing via laser cladding, high temperature gradients and rapid cooling rates can easily induce significant non-equilibrium solidification. For complex alloy systems containing high chromium, high molybdenum, and added niobium, silicon, hafnium, and carbon, the coordinated control of parameters across multiple process steps is challenging. If the thermodynamic field constructed during pretreatment is mismatched with the transient heat input of the laser, significant residual thermal stress can easily occur at the interface between the substrate and the deposited layer. Furthermore, if the extreme melting point difference between niobium and silicon in the raw materials is not effectively controlled within the transient laser molten pool, a significant thermodynamic barrier can easily induce significant macroscopic chemical segregation and a dense hot crack network.

[0030] To provide a good interfacial metallurgical foundation for subsequent laser melting, the prepared flange chassis substrate needs to undergo thermodynamic pretreatment to construct a low-temperature gradient initial field.

[0031] In step S1, the matrix material is selected from high-yield-strength heat-resistant alloy forgings or homogeneous nickel-based alloy plates, which are used to provide the basic structural strength to support heavy steel coils in a high-temperature annealing furnace. A dense matrix blank is obtained by a high-tonnage forging process, and then CNC machining is used to cut it to the design dimensions.

[0032] After molding, the matrix needs to undergo solution treatment and stress-relief annealing to alleviate the internal dislocation entanglement and grain boundary residual stress concentration introduced by the previous plastic deformation and machining. The matrix is ​​placed in a controlled atmosphere heat treatment furnace and held at a temperature range of 1050~1100℃ for 120~180min, and then cooled to room temperature by flowing air. The above thermal cycling process promotes static recrystallization and element homogenization diffusion of deformed grains inside the matrix, reduces grain boundary distortion energy and restores the macroscopic impact plasticity of the material.

[0033] In addition, the surface condition of the pretreated substrate was evaluated and roughened. After confirming that there were no macroscopic cracks or shrinkage cavities in the substrate by high-frequency ultrasonic non-destructive testing, alumina ceramic particles with a particle size of 50~100μm were used as the sandblasting medium to carry out high-pressure airflow surface bombardment to peel off the micro-oxide scale and fatigue-processed modified layer on the surface, and control the surface roughness Ra in the range of 6.3~12.5μm. The micro-rough morphology can increase the solid-liquid contact wetting area of ​​the liquid alloy during subsequent laser transient melting, and improve the shear peeling resistance of the composite coating through mechanical micro-interlocking effect.

[0034] In addition, the surface-modified substrate is fixed in the constant temperature heating platform of the laser additive manufacturing equipment chamber for preheating treatment; the preheating temperature is set to 400~450℃ and kept constant for 10-12 hours, so that the heat energy can be uniformly penetrated into the three-dimensional nodes inside the large-volume substrate through solid-state heat conduction, thereby constructing a uniformly distributed thermodynamic initial field.

[0035] Preferably, the thermodynamic parameter control of the above-mentioned overall substrate preheating process is constrained by the evolution of transient thermal stress in the material, and its quantitative relationship is expressed by the following formula: ,in, This represents the transient residual thermal stress at the material interface. This represents the elastic modulus of the substrate material under the corresponding temperature gradient. This represents the coefficient of linear thermal expansion of the substrate material. This represents the absolute temperature difference between the laser transient molten pool and the solid substrate. The material's Poisson's ratio is a dimensionless physical constant.

[0036] Preferably, by raising the overall temperature of the matrix to 400~450℃, the absolute temperature difference between the laser transient molten pool and the solid substrate is significantly reduced, thereby effectively reducing the residual thermal stress during the non-equilibrium solidification process at the interface from a mechanical source. At the same time, the aforementioned thermodynamic initial field reduces the ratio of the temperature gradient to the solidification cooling rate at the solid-liquid interface of the molten pool, alleviates the compositional supercooling effect of large atomic radius elements that are prone to segregation in the alloy melt, suppresses the epitaxial growth of the primary strengthening phase in the form of coarse, straight columnar crystals towards the solidification front of the molten pool, significantly promotes the formation trend of isotropic equiaxed crystals, and effectively blocks the physical channel for the rapid propagation of hot cracks along continuous grain boundaries at the microstructure level.

[0037] The preparation of modified alloy powder in step S2 is the foundation for improving the macroscopic mechanical properties and directional control of microstructure of the flange chassis in the subsequent laser additive manufacturing process. At the composition design level, the dependence of traditional ultra-high temperature alloys on rhenium is reduced. Using IN738LC high temperature alloy as the matrix composition framework, microalloying modification by the synergistic effect of four elements, niobium, silicon, hafnium and carbon, is introduced.

[0038] Specifically, the chemical composition of the modified alloy powder ranges by mass percentage as follows: chromium 15.5%~16.4%, cobalt 8.0%~9.0%, molybdenum 2.5%~3.5%, tungsten 3.0%~4.0%, aluminum 4.5%~5.2%, titanium 2.4%~3.7%, and tantalum 3.0%~4.0%. The modified components include niobium (1.5%–2.5%), silicon (0.3%–0.6%), hafnium (0.1%–0.3%), carbon (0.12%–0.18%), boron (0.01%–0.02%), and zirconium (0.02%–0.08%). The remaining components are nickel matrix and trace impurities that are difficult to completely avoid during the smelting and processing.

[0039] The composition range is established through phase diagram thermodynamic calculations and solidification kinetics evaluation to ensure that each element achieves the designed distribution and expected phase composition under non-equilibrium solidification conditions.

[0040] Furthermore, the aforementioned alloy powder was prepared using high-vacuum induction melting gas atomization technology to ensure the physical flowability and chemical compatibility of the powder during subsequent laser high-energy beam additive manufacturing. During the preparation process, according to the preset chemical composition ratio, high-purity elemental metal raw materials or intermediate alloys of each component were weighed, induction heating was initiated, and each component high-purity elemental metal raw material or intermediate alloy was placed under a vacuum degree better than 1×10⁻⁶. -3 In Pa's induction melting furnace, the furnace temperature is raised to the range of 1500℃~1600℃ to completely melt the raw materials. Under high temperature molten conditions, the electromagnetic field generated by the induction coil is used to continuously stir the molten pool, so that niobium and hafnium elements with high melting point characteristics can achieve atomic-level diffusion and uniform distribution in nickel-based liquid metal, eliminating chemical composition fluctuations caused by macroscopic segregation.

[0041] After smelting, the homogenized high-temperature alloy melt enters the high-pressure atomizing cooling tower in a stable laminar flow state through the bottom guide pipe. Using nitrogen fluid with a driving pressure of 5~8MPa and a purity of ≥99.99%, the vertically falling liquid metal stream is subjected to supersonic impact, inducing the melt to break into micro-droplets. During the descent of the gas atomizing tower, the droplets spontaneously spheroidize under the action of surface tension and rapidly solidify to form micro-solid metal powder particles. The solidified powder is collected by the collector at the bottom of the tower and transported to a closed ultrasonic vibration sieving system. Through the physical interception action of multi-stage ultrasonic screens, the powder is physically intercepted and its particle size is controlled, keeping the powder particle size distribution range within the continuous operating range of 15~53μm.

[0042] The selected powder group has good microscopic three-dimensional morphology characteristics, with the statistical sphericity of individual powder particles ≥95%, and the macroscopic powder flowability index is stably controlled within the range of Hall flow rate ≤15s / 50g. The above flow characteristics can improve the macroscopic flatness and microscopic packing density of powder in the powder spreading device of laser additive manufacturing equipment, providing an important material basis for the stable expansion of the subsequent ultra-fast non-equilibrium solidification molten pool.

[0043] During the powder preparation process, retaining the inherent high chromium and high molybdenum content in the IN738LC base alloy has important high-temperature physicochemical significance; the synergistic effect of 15.5~16.4% chromium element with silicon and niobium elements in the modified system is to build a chemical protective barrier for the material to resist ultra-high temperature oxidation at 1200℃ and complex atmospheric thermal corrosion environment.

[0044] During the initial high-temperature service phase, elements with different oxidation potentials within the matrix selectively and directionally diffuse long distances to the outer surface of the material under the drive of thermal activation energy. They react chemically with free oxygen molecules in the external environment, forming a three-layer self-healing composite oxide film in situ on the outer surface of the functional host layer. Specifically, the oxidation kinetics are as follows: silicon atoms, with the strongest affinity for oxygen, preferentially form an amorphous SiO2 inner oxide layer in situ on the alloy matrix surface to impede the interfacial oxygen partial pressure gradient; high-concentration chromium atoms then form a dense and thermodynamically stable Cr2O3 main protective layer on the outer side of the SiO2 inner oxide layer; simultaneously, highly reactive niobium elements diffuse outwards and undergo further composite oxidation with some silicon elements on the outer side of the main protective layer, generating a Nb2O5-SiO2 composite self-healing layer with the ability to fill cracks at high temperatures. The growth kinetics and interlayer physicochemical matching of these three oxide films effectively block the long-range diffusion channels of external oxygen atoms into the alloy matrix.

[0045] Furthermore, molybdenum, with a mass fraction of 2.5–3.5%, has a larger atomic radius than nickel atoms. Its substitution process in the nickel-based face-centered cubic lattice leads to local microscopic lattice distortion. The internal stress field induced by atomic size mismatch can produce a significant solid solution strengthening effect. The molybdenum atoms distributed inside the crystal can increase the elastic strain energy barrier for dislocations to move within the slip plane and climb over obstacles, thereby improving the yield strength and resistance to macroscopic plastic flow of the alloy matrix under extreme high-temperature tensile conditions.

[0046] Furthermore, the technological path that breaks through traditional understanding of this raw material lies in the precise quantitative introduction and synergistic control of niobium and silicon elements at the interface. Within the traditional physical metallurgical framework, niobium and silicon elements exhibit a strong tendency for micro-segregation during the solidification of liquid metal, and tend to accumulate in the interdendritic region of the final solidification, thereby inducing the precipitation of large-volume brittle topological close-packed phases such as σ phase or μ phase, resulting in a significant decrease in the material's resistance to low-cycle fatigue.

[0047] However, in the modified structure constructed in this invention, 1.5–2.5% niobium and 0.3–0.6% silicon by mass form a significant ternary composite interface strengthening effect. A small portion of niobium atoms preferentially dissolve in the γ matrix to exert a conventional lattice distortion strengthening effect, while most of the enriched niobium atoms have strong carbon affinity kinetics. During rapid laser solidification and subsequent composite heat treatment, they combine with carbon elements in the system, precipitating in situ at the micrograin boundaries as MC-type carbide nanoparticles with high melting points and Vickers hardness. The precise introduction of trace amounts of silicon induces thermodynamic reconstruction of the strengthening phase interface within the matrix. Driven by thermodynamics, silicon atoms preferentially segregate at the coherent interface between the γ matrix and the γ' main strengthening phase. The physical essence of this segregation behavior lies in reducing the lattice mismatch at the phase interface. The significant decrease in interfacial energy induced by silicon can improve the thermodynamic stability of the γ' phase, raising its macroscopic remelting temperature limit to a high-temperature range above 1250°C, thus alleviating the structural problem of the main strengthening phase dissipation under high-temperature conditions.

[0048] To mitigate the risks of interdendritic solidification hot cracking and brittle phase network formation that may result from the introduction of niobium and silicon, hafnium (0.1–0.3% by mass) was introduced into the modified raw material system based on phase diagram calculations, and the carbon content was increased to the range of 0.12–0.18%. Due to its large atomic radius and unique electronic structure, hafnium encounters significant interfacial propulsion solid-liquid partitioning resistance during laser non-equilibrium transient solidification, resulting in significant interdendritic local segregation at the solidification front. Hafnium atoms enriched in the residual liquid film region at the end of solidification undergo a multi-element eutectic reaction with niobium and silicon in the same region, generating intermetallic compounds with high melting temperatures and a discontinuous, island-like distribution. The hard points of the high-melting-point compounds form a rigid support structure in the residual liquid film, bearing and dissipating the tensile stress accumulated in the material during the late solidification shrinkage stage, thus inhibiting the microscopic propagation of intergranular hot cracks from a physical and mechanical perspective.

[0049] Simultaneously, trace amounts of hafnium alter the stoichiometric ratio of the harmful Laves phase at grain boundaries, promoting its in-situ topological evolution from a traditional ternary intermetallic compound with high hardness and brittleness to a complex hafnium-containing phase exhibiting intrinsic micro-toughness at both room temperature and high temperature. This reduces the probability of stress concentration during microcrack nucleation at the phase interface. Combined with the increased carbon content, the system establishes a sufficient carbon diffusion flux in the early stages of new phase nucleation, consuming residual free niobium atoms in the later stages of solidification. This suppresses the thermodynamic nucleation tendency of brittle topologically close-packed phases from the perspective of chemical potential driving force.

[0050] After completing the thermodynamic pretreatment and surface roughening modification of the flange chassis substrate to construct a uniform and stable initial thermodynamic field, and preparing IN738LC-based modified alloy powder with good fluidity, compositional uniformity, and high-temperature strengthening potential, the laser melting core preparation stage can begin. To achieve metallurgical bonding between the substrate and subsequent deposition layers, alleviate residual thermal stress at the interface, and lay the foundation for reverse segregation control and the construction of an anti-creep main structure, a first-stage laser melting treatment needs to be performed on the substrate surface based on the established initial thermodynamic field to form a transition layer and precursor.

[0051] In step S3, a first-stage laser melting process is performed on the alloy powder using a high-energy laser selective melting process or a high-energy laser direct deposition process to construct the metallurgical transition layer and its precursor microstructure. By controlling the non-equilibrium solidification dynamics state and the in-situ physicochemical reaction of the gas-liquid-solid multiphase flow field in the transient molten pool, the large-area intergranular hot crack defect network that is prone to form in highly alloyed mixed powders under extreme cooling rates is eliminated at the micro-metallurgical physical level.

[0052] Specifically, a high-energy laser generator emits a laser beam and scans and melts it on the powder layer on the forming stage. During this process, the output power of the high-energy laser generator is 220~280W, the spot diameter at the laser focal point is 100~120μm, the thickness of the powder layer on the forming stage is 25~35μm, and the laser beam scanning speed is 600~800mm / s.

[0053] Compared to conventional high-strength nickel-based alloy additive manufacturing processes with scanning speeds greater than 1000 mm / s, the laser beam scanning speed of 600~800 mm / s reduces the instantaneous linear energy scanning rate. This reduction in the instantaneous linear energy scanning rate extends the lifespan of the molten metal in the high-temperature transient liquid pool from a thermodynamic and heat transfer perspective. This extended lifespan slows down the rate at which the solidification front at the solid-liquid interface advances towards the center of the pool. This slowdown in the rate at which the solidification front advances towards the center of the pool provides a time evolution window for in-situ multiphase chemical reactions and provides enthalpy energy reserves for the self-healing rheological dynamics of the micro-dendritic interlayer liquid film interface.

[0054] In the first stage of laser melting for multi-layer transition metallurgy, the protective atmosphere inside the sealed chamber of the processing equipment is prepared with a trace amount of reactive mixed gas. In the traditional high-temperature high-strength alloy high-energy beam additive manufacturing process, in order to prevent the burning of high-temperature active metal elements and the generation of a large number of non-metallic oxide inclusions, the residual free oxygen content in the processing chamber is usually controlled to an oxygen-free environment of less than 10 ppm.

[0055] This invention uses high-purity industrial nitrogen as the basic inert protection and hydrodynamic exhaust carrier, and introduces trace amounts of reactive gas into the processing chamber through a gas mass flow controller system. The gaseous volume fraction of oxygen in the mixed fluid protective atmosphere is 50~150ppm, and the spatial volume fraction of nitrogen is 50~100ppm. The trace reactive two-phase gas in-situ doping strategy can induce and guide a series of interfacial physicochemical in-situ reactions with micro-metallurgical strengthening value in the ultra-high temperature metal plasma strong radiation flow field triggered by the laser beam. This provides a free energy chemical potential driving force for the activation of the crack resistance and toughening physics of the internal microstructure of the multilayer transition metallurgical layer.

[0056] The controllable introduction of trace amounts of gaseous nitrogen atoms into a mixed inert protective atmosphere regulates the in-situ nucleation of high-melting-point nanoscale precipitated strengthening phases within the micro-melt and the refinement and evolution of primary grains during the early stages of solidification. The peak temperature at the center of the laser photon-induced transient high-energy micro-melt pool can exceed 2000℃, accompanied by localized boiling and eruption of liquid metal vapor and the formation of high-pressure plasma plumes. Under the collision of short-wavelength thermal radiation fields and high-energy electrons, the trace amounts of diatomic molecular nitrogen gas introduced in the mixture undergo covalent bond dissociation and breakage. Nitrogen gas, in a highly chemically reactive monatomic state, rapidly penetrates and dissolves into the depths of the liquid multi-component nickel-based alloy fluid.

[0057] The niobium element added to the pre-formed composite raw material powder has a strong thermodynamic affinity with free dissolved nitrogen atoms; under the dual drive of thermocapillary convection and Marangoni surface tension gradient flow field inside the molten pool, the niobium element and free dissolved nitrogen atoms rapidly meet at a microscopic level; the niobium element and free dissolved nitrogen atoms spontaneously undergo a chemical reaction in situ inside the melt, rapidly precipitating a large number of spherical niobium nitride (NbN) nanoceramic particles with a size distribution in the range of 10~50 nm.

[0058] In traditional powder metallurgy processes, the introduction of externally added nano-reinforcing particles through external physical-mechanical ball milling and mixing methods can easily lead to severe agglomeration and compositional segregation. In contrast, nano-niobium nitride reinforcing particles synthesized in situ within the deep fluid of liquid metal can be uniformly dispersed throughout the three-dimensional space of the entire transient molten pool. The in-situ generated hard nanoparticles and the rapidly cooled nickel-rich face-centered cubic gamma solid solution metal matrix form a coherent or semi-coherent phase interface with high lattice matching. The atomic-level matching between the niobium nitride nano-ceramic particles and the nickel-rich face-centered cubic gamma solid solution metal matrix reduces the interfacial energy barrier and local volume expansion strain energy during the precipitation of new phases.

[0059] After the laser focus is removed, the dispersed and suspended nano-nitride particles solidify as the transient molten pool rapidly cools and undergoes a phase transition. The nano-nitride particles act as a dense heterogeneous nucleation core, which promotes the refinement of the size of the nascent solid grains at the solid-liquid phase transition front. This process blocks and breaks down the coarse, straight columnar crystal structure that originally tended to grow along the high-temperature gradient, transforming it into a fine, uniform, and non-directional equiaxed microcrystalline structure. The equiaxed microcrystalline structure enhances the isotropic plastic deformation capacity and macroscopic tensile fracture toughness of the transition layer.

[0060] In the late stage of laser non-equilibrium ultra-rapid solidification, complex multi-principal element high alloy systems are prone to mechanical tearing of the interdendritic micro-liquid film due to the unbalanced segregation of solid solution solute elements. In this process, trace amounts of oxygen controlled in the concentration range of 50~150ppm have interfacial rheological and thermodynamic intervention effects. When the transient micro-melt pool temperature drops exponentially and rapidly and enters the solid-liquid two-phase coexistence region, i.e. the end of the paste-like solidification stage, active alloying elements such as niobium and silicon, which have extremely low solid-liquid equilibrium distribution coefficients, are driven out by the micro-repulsive force at the crystallization front and enriched in the micro-region of the residual high-temperature liquid phase film between dendrites.

[0061] Trace amounts of highly reactive oxygen atoms dissolved deep within the molten metal undergo rapid redox chemical reactions with the highly concentrated niobium and silicon elements in the region, generating in situ a certain amount of nanoscale multi-element composite oxide particles with thermodynamic stability and intrinsic hardness. Simultaneously, hafnium elements segregated in the dendrite interstices undergo in-situ eutectic reactions with niobium elements under the drive of local supercooling and chemical potential gradients, generating highly stable high-melting-point compounds HfNb2. These nanoscale composite oxide particles are dispersed and suspended at the solid-liquid interface at the solidification front, where they spatially interweave and chemically bond with the eutectic high-melting-point compounds HfNb2.

[0062] Nanoscale composite oxide particles and high-melting-point compound HfNb2 together construct a microscopic three-dimensional support framework with good spatial continuity and mechanical rigidity within the interdendritic fluid channels. This framework structure, jointly anchored by the two, can stabilize the free, active, and hydrodynamically unstable interdendritic thin liquid film phase interface, increase the surface tension of the high-temperature microscopic liquid film system at the end of solidification, and enhance its stability against external tensile stress shear deformation.

[0063] The continuous interdendritic network constructed by the multiphase composite ceramic particle network and the residual high-temperature liquid metal phase possesses tensile stress resistance and can trigger a self-healing liquid film effect at the microscale. When the transition layer undergoes a drastic volume solidification and shrinkage process from a high-temperature liquid state to a room-temperature solid state, a macroscopic and microscopic shrinkage tensile stress network is generated inside, which easily forms the nucleation prototype of microscopic thermal cracks at the solid-liquid interface between dendrites by utilizing the stress concentration effect.

[0064] A reinforced modified liquid film network with high interfacial surface tension and a robust supporting framework can resist the mechanical tearing effect of initial micro-tensile stress due to the rigidity of the framework. Simultaneously, utilizing the newly generated micro-initial gap space, it generates a capillary pumping effect following the laws of microfluidics. The micro-nano-scale capillary negative pressure difference generated by the capillary pumping effect can rapidly draw in and guide the high-temperature residual liquid metal fluid rich in solute elements around the gap, which is not yet fully crystallized and solidified, to the depths of the micro-gap about to crack and propagate, achieving dynamic backfilling of liquid metal and healing of solidification cracks. The in-situ spontaneous healing of grain boundaries, dominated by the surface tension potential energy of the alloy's internal microfluidics, can change the phenomenon of irreversible high-speed propagation along grain boundaries after micro-cracks exceed the critical nucleation size in traditional high-internal-stress additive manufacturing processes.

[0065] After completing the high-density, equiaxed, and stable precursor transition layer, the flange chassis fabrication process overcomes interfacial hot crack defects and transitions to the continuous stacking and molding stage of the functional host layer. Step S4, based on the substrate thermophysical properties determined in step S1 and the microchemical characteristics of the raw material powder in step S2, continues with multi-layer, multi-pass laser melt deposition to construct the functional host layer; This step implements reverse segregation microstructure engineering, employing different process parameters from step S3 to trigger non-equilibrium solidification conditions. These parameters include: laser power 220–280 W, scanning speed 700–1000 mm / s, spot diameter 100–120 μm, powder layer thickness 25–35 μm, scanning spacing 0.08–0.10 mm, and a scanning strategy of helical scanning with 90° interlayer rotation. The synergistic matching of these process parameters controls the laser energy density to 55–75 J / mm². 3 And increase the molten pool cooling rate to 10 4 ~10 5 K / s; Under cooling, the embrittlement tendency of niobium and silicon is transformed into an interwoven structure composed of high-strength main dendrites and high-toughness interdendritic networks, thereby improving the creep fatigue life of the material at 1200℃.

[0066] After completing the construction of the underlying metallurgical transition layer and precursor, multi-layer, multi-pass laser melting deposition is carried out based on the thermophysical properties of the substrate and the microchemical characteristics of the raw material powder to construct the functional main layer of the flange chassis, so as to bear large static loads and resist high-temperature environments. Through reverse segregation microstructure engineering, the solute partitioning behavior of niobium and silicon is transformed into structural reinforcement to improve the material's resistance to creep fatigue by utilizing non-equilibrium thermodynamics.

[0067] To stimulate microscopic physicochemical effects, this step constrains the volumetric energy density of the laser-driven molten pool to 55–75 J / mm². 3 Within the process window, a high local temperature gradient is triggered in the molding zone, which, combined with substrate heat conduction, induces 10 4 ~105 Non-equilibrium cooling rate (K / s).

[0068] A higher physical cooling rate alters the thermodynamic distribution behavior and diffusion path of solute atoms at the solid-liquid phase transition front. In conventional high-temperature alloy casting processes, the equilibrium distribution coefficients of alloying elements such as niobium and silicon in nickel-based solid solutions are less than the theoretical critical values. As the primary solid phase grows, they are repelled and enriched in the interdendritic region. Conventional segregation leads to insufficient yield strength of the dendritic trunk core, and macroscopic embrittlement occurs between dendrites due to the precipitation of brittle intermetallic compounds. Under the conditions of this invention, the liquid metal to solid lattice transition rate exceeds the solute atom diffusion rate, triggering a solute trapping effect. The solute distribution coefficient at the solid-liquid phase transition interface shifts from the equilibrium threshold with increasing solidification rate, inducing reverse segregation grain boundary reconstruction.

[0069] Reverse segregation engineering utilizes the forward segregation tendency of niobium; the spatial temperature gradient generated by the movement of the laser beam drives the segregation coefficient of niobium to reach 1.5~2.0, causing large atomic radius niobium to be trapped in the core of the primary dendrite trunk; high concentration of niobium reacts with carbon, and dispersed NbC niobium carbide nanoparticles are precipitated in situ within the dendritic lattice; the niobium-reinforced dendritic trunk structure composed of niobium enriched by forward segregation and precipitated NbC carbides increases the yield strength by hindering dislocation movement, and impedes the dislocation shear and plastic flow caused by grain boundary slip under the high temperature and heavy load of 1200℃ on the flange chassis.

[0070] Microstructure control engineering regulates the negative segregation of silicon; volumetric energy density constraints stabilize the silicon segregation coefficient at 0.5~0.7, and highly diffusive silicon is displaced and enriched in the interdendritic liquid film region; high-concentration silicon at grain boundaries undergoes eutectic reaction with hafnium and residual niobium to generate thermodynamically stable silicides such as pentasilicide niobium and disilicide; the silicides maintain lattice stability at a high temperature of 1200℃, and the rheological properties of the interdendritic layer are changed through the grain boundary pinning effect, thus constructing a microscopic defense line with high resistance to shear slip.

[0071] A high-strength and high-toughness functional main body layer for the flange chassis was constructed through high-energy beam fusion deposition and microscopic reverse segregation engineering. However, rapid thermal cycling deposited a high residual tensile stress network inside, while brittle phases such as σ phase and Laves phase emerged deep within the grain boundaries. If directly subjected to a high-temperature, heavy-load environment of 1200℃ without thermodynamic intervention, the brittle phases would degenerate into creep cavities and crack propagation channels. Step S5 involves composite post-processing, which uses a multi-order temperature gradient field and a high-pressure stress field to synergistically intervene, achieving brittle phase transformation and homogenization reconstruction of the grain boundary network to improve the high-temperature creep resistance of the component.

[0072] In step S5, the post-processing includes: hot isostatic pressing, directional recrystallization, and two-stage aging.

[0073] The product is processed in a hot isostatic pressing furnace; the process parameters are a high temperature of 1200~1240℃, a high pressure of 180~220MPa nitrogen environment, and holding at this temperature for 3~4 hours, followed by furnace cooling at a rate of ≤30℃ / h. This high-temperature, ultra-high-pressure extreme environment utilizes the macroscopic plastic creep closure effect of metallic materials and the long-range diffusion dynamics of solid-solid atoms within the crystal to compact and bridge microscopic defects such as micron-level interdendritic pores and incomplete interlayer fusion that are difficult to avoid during the layer-by-layer scanning process of high-energy beam additive manufacturing, thus improving the macroscopic... The theoretical density is improved; the high temperature and high pressure fluid thermodynamic boundary conditions promote the cross-grain boundary homogenization diffusion of multi-principal high-concentration alloying elements, smooth out the local solute concentration fluctuations caused by the extreme non-equilibrium solidification in the early stage, and promote the thermodynamically driven local re-dissolution of the primary, irregularly shaped coarse σ phase and grain boundary Laves phase in the laser-deposited microstructure. This provides energy reserves and a highly homogenized supersaturated solid solution substrate for the subsequent re-homogenization and nucleation of microphases and fine control of topology at specific aging temperatures.

[0074] The product after ultra-high pressure hot isostatic pressing is transferred to a directional isothermal heat treatment furnace. The flange base is placed in the central heating zone of the furnace, where the physical temperature is controlled at 1240~1270℃. This temperature range of 1240~1270℃ is above the complete dissolution temperature line of the main strengthening phase, the gamma-ray phase, within the matrix, and is close to the critical thermodynamic sensitive window of the alloy's intrinsic solidus line. Under high thermodynamic energy critical conditions, a directional dynamic temperature gradient flow field is applied within the material matrix by uniformly translating the external electromagnetic heating zone or mechanically tractioning the internal sample. The traction rate of the directional dynamic temperature gradient flow field is 15~25 mm / h. Subsequently, controlled cooling is performed at a fluid cooling rate of 5~10℃ / min. The thermodynamic phase transition activation energy and the uniaxial directional thermal potential gradient jointly drive secondary recrystallization within the material. The objects of secondary recrystallization include small equiaxed crystal networks and spatially disordered primary columnar crystal clusters. Secondary recrystallization is a microscopic abnormal grain growth phenomenon. At large-angle microscopic grain boundaries, atoms undergo rapid directional migration and rearrangement along the macroscopic heat flow direction. After this migration and rearrangement, a large number of coarse columnar crystal microstructures are generated within the macroscopic volume of the component. The crystallographic orientation of the principal axes of these coarse columnar crystals is parallel to the main force axis of the flange base. The microcrystalline physical structure formed by the thermodynamic reconstruction of the directional flow field reduces the number of transverse weak grain boundaries at the geometric and topological level. Transverse weak grain boundaries refer to grain boundaries perpendicular to the macroscopic applied static tensile stress axis.

[0075] Two-stage precise aging treatment is applied to components that have undergone directional recrystallization and microstructure reconstruction to achieve final shaping of the internal microstructure geometry of the material matrix and optimization of precipitation-strengthened dislocation retardation; this includes a first-stage physical aging treatment and a second-stage isothermal aging treatment.

[0076] Specifically, the parameters for the first-stage physical aging are: treatment temperature 1120℃, and holding time 4-6 hours. The long-term high-temperature exposure at 1120℃ induces the spontaneous precipitation of a primary γ′ strengthening phase within the high-temperature nickel-based solid solution. This primary γ′ strengthening phase exhibits a regular octahedral or cubic morphology, with a size concentrated between 300-500 nm. Simultaneously, the long-term high-temperature exposure at 1120℃ implements interfacial phase transformation kinetics control over the easily precipitated σ phase in the high-chromium alloy metallurgical system. The prior thermodynamic high-temperature remelting intervention and the constraint of the first-stage aging temperature of 1120℃ limit the thermodynamic driving force for σ phase nucleation and the microscopic advancement rate of the phase interface. Combined with the residual local concentration fluctuations in the micro-regions of modified niobium and trace silicon elements introduced earlier at specific micro-grain boundaries, the brittle σ phase will not grow in a coarse, plate-like morphology that disrupts the geometric continuity of the crystal. The brittle σ phase is transformed into ultrafine nanoscale polygonal particles with an equivalent size of 50~200 nm through in-situ thermodynamic topological evolution. These ultrafine nanoscale polygonal σ phase particles are densely precipitated at the microscopic grain boundary network in a highly discontinuous and uniform spatial distribution. The σ phase modified by nano-size eliminates the structural characteristics that easily induce macroscopic cleavage and brittle fracture of the material. The Vickers hardness of the nanoscale σ phase is between 700 and 1000 HV, and it can be used as a nano-reinforcing phase particle with a strong grain boundary dislocation hindrance effect. The nanoscale σ phase particles pin the macroscopic grain boundary slip interface and improve the shear deformation yield strength of the macroscopic grain boundary under ultra-high temperature conditions of 1200℃.

[0077] After the first-stage physical aging treatment, the system temperature gradually decreased to 850℃. At 850℃, a second-stage isothermal aging treatment was then carried out for 10–15 hours. This prolonged low-temperature thermal exposure at 850℃ induced the precipitation of near-spherical secondary γ′ phase microparticles within the continuous narrow channels of the face-centered cubic matrix. The equivalent size of these near-spherical secondary γ′ phase microparticles was less than 50 nm, exhibiting fine and uniform characteristics. These microparticles, together with the previously generated coarse primary γ′ phase, constituted a bimodal distribution pattern. The microscale range of this bimodal distribution pattern was reasonable. From the micromechanical perspective of multi-scale dislocation cutting and bypassing interactions, the bimodal distribution pattern enhanced the macroscopic comprehensive precipitation strengthening effect of the material matrix.

[0078] Meanwhile, the 850℃ low-temperature range is a key interfacial thermodynamic window for regulating the microchemical and topological transformation of the residual Laves phase at the grain boundaries. The cobalt, hafnium and other elements introduced into the composite gas atomization raw material powder in the early stage have undergone partial lattice substitution with the nickel element in the matrix, which has caused a thermophysical transformation of the initial crystal structure of the traditional harmful Laves phase. Under the long-term constant thermal activation energy at 850℃, the surface energy of the grain boundary interface tends to be minimized, which promotes the spontaneous topological restructuring and spherical morphological evolution of the complex Laves phase modified by multi-element microchemistry. The above evolution transforms the Laves phase in situ at the microscale into the crystallographically stable (Ni,Co,Hf)2(Nb,Si) type Laves phase. The (Ni,Co,Hf)2(Nb,Si) type Laves phase with a specific chemical ratio gradually evolves from an irregular network or sharp polygonal block morphology continuously distributed along grain boundaries into geometrically smooth ellipsoidal or near-spherical precipitate clusters. The highly geometrically spheroidized modified (Ni,Co,Hf)2(Nb,Si) type Laves particles are highly dispersed and embedded in the vicinity of the complex dendrite spacing and the intersection of the three grain boundaries. From the perspective of microscopic interface fracture mechanics, it eliminates the harmful effect as a potential source of microscopic tensile crack initiation and transforms into a spherical dislocation pinning strengthening phase in the functional host layer that can inhibit the long-range climbing motion of dislocation lines in the matrix. Moreover, the spherical dislocation pinning strengthening phase effectively suppresses the tendency of the material to undergo intergranular cleavage fracture under high temperature and heavy load.

[0079] Exemplary device: A creep-resistant laser melting flange chassis includes: The flange base plate is a heat-resistant alloy forging that has undergone high-temperature solution treatment and stress-relief annealing. It is used to provide the basic structural strength for bearing heavy steel coils in a high-temperature annealing furnace. The transition layer is metallurgically bonded to the surface of the flange base plate. The transition layer contains in-situ generated NbN nanoparticles with a size of 10~50nm. The micro-dendritic intergranular structure has a self-healing liquid film network structure composed of nano-scale composite oxides and high-melting-point compound HfNb2, which is used to refine the grains and relieve the interfacial thermal stress between the substrate and the upper structure. The functional main layer is stacked on top of the transition layer. The functional main layer is an anti-creep core working layer formed by laser melt deposition and post-processing of rhenium-free high-chromium nickel-based alloy powder containing niobium, silicon, hafnium and carbon. The functional host layer has a specific reverse segregation microstructure, including niobium-reinforced dendrites composed of niobium elements enriched by positive segregation and precipitated NbC carbides, and silicon-reinforced interdendritic structures composed of silicon elements enriched by negative segregation and formed high-melting-point silicides. The functional host layer has a discontinuous distribution of nanoscale σ-reinforcing phases with a size of 50~200nm at the grain boundaries, as well as spherical (Ni,Co,Hf)2(Nb,Si) type Laves dislocation pinning phases formed by hafnium modification; Under high-temperature service conditions, the outer surface of the functional main layer is in situ formed with three layers of self-healing composite oxide film, which are, from the inside to the outside, an amorphous SiO2 inner oxide layer, a dense Cr2O3 main protective layer, and an Nb2O5-SiO2 composite self-healing layer with the ability to fill cracks at high temperatures.

[0080] Example 1: A method for preparing a creep-resistant laser melting flange base, comprising the following steps: S1. Prepare the flange base plate by forming a heat-resistant nickel-based alloy forging and machining it to the design dimensions; place the base plate in a heat treatment furnace, hold it at 1080℃ for 150 min and then air cool it; then sandblast it with alumina ceramic particles with a particle size of 80μm to achieve a surface roughness Ra of 8.5μm; finally, fix the base plate on a heating platform and preheat it at a constant temperature of 420℃ for 12 h.

[0081] S2. Prepare modified alloy powder with the following chemical composition by mass percentage: Cr 16.0%, Co 8.5%, Mo 3.0%, W 3.5%, Al 4.8%, Ti 3.0%, Ta 3.5%, Nb 2.0%, Si 0.45%, Hf 0.2%, C 0.15%, B 0.015%, Zr 0.05%, with the balance being Ni; prepared using high-vacuum induction melting gas atomization technology, with the powder particle size controlled between 15 and 53 μm.

[0082] S3. Perform the first stage of laser melting on the substrate surface. The process parameters are: laser power 250W, scanning speed 700mm / s, spot diameter 110μm, powder layer thickness 30μm; the protective atmosphere is nitrogen substrate, with oxygen content of 100ppm and nitrogen content of 80ppm.

[0083] S4. The second stage of laser melting is carried out to construct the functional main layer. The process parameters are: laser power 250W, scanning speed 850mm / s, spot diameter 110μm, powder layer thickness 30μm, scanning spacing 0.09mm, and spiral scanning with 90° rotation between layers is adopted.

[0084] S5. Post-treatment: First, hot isostatic pressing is performed under the following conditions: 1220℃, 200MPa, holding for 3.5h, with a furnace cooling rate ≤30℃ / h. Then, directional recrystallization is performed under the following conditions: heating zone 1250℃, traction rate 20mm / h, cooling rate 8℃ / min. Finally, two-stage aging is performed under the following conditions: first stage holding at 1120℃ for 5h, and second stage holding at 850℃ for 12h.

[0085] Example 2: A method for preparing an anti-creep laser melting flange chassis. The similarities with Example 1 will not be repeated. The difference is that in step S2, the Nb content of the modified alloy powder is 1.5%.

[0086] Example 3: A method for preparing an anti-creep laser melting flange chassis. The similarities with Example 1 will not be repeated. The difference is that in step S2, the Nb content of the modified alloy powder is 2.5%.

[0087] Example 4: A method for preparing an anti-creep laser melting flange base plate, which is the same as Example 1 and will not be repeated. The difference is that in step S4, the scanning speed is 700 mm / s.

[0088] Example 5: A method for preparing an anti-creep laser melting flange base, which is the same as Example 1 and will not be repeated here. The difference is that in step S4, the scanning speed is 1000 mm / s.

[0089] Example 6: A method for preparing an anti-creep laser melting flange chassis. The similarities with Example 1 will not be repeated. The differences are: in step S2, the Hf content is 0.1%; in step S3, the oxygen content of the protective atmosphere is 50 ppm.

[0090] Example 7: A method for preparing an anti-creep laser melting flange chassis. The similarities with Example 1 will not be repeated. The differences are: in step S2, the Hf content is 0.3%; in step S3, the oxygen content of the protective atmosphere is 150ppm.

[0091] Comparative Example 1: A method for preparing an anti-creep laser melting flange chassis, which is the same as Example 1 and will not be repeated here. The difference is that in step S2, the Nb content of the modified alloy powder is 1.4%.

[0092] Comparative Example 2: A method for preparing an anti-creep laser melting flange chassis, which is the same as Example 1 and will not be repeated here. The difference is that in step S2, the Nb content of the modified alloy powder is 2.6%.

[0093] Comparative Example 3: A method for preparing an anti-creep laser melting flange base, which is the same as Example 1 and will not be repeated here. The difference is that in step S4, the scanning speed is 650 mm / s.

[0094] Comparative Example 4: A method for preparing an anti-creep laser melting flange base, which is the same as Example 1 and will not be repeated here. The difference is that in step S4, the scanning speed is 1050 mm / s.

[0095] Comparative Example 5: A method for preparing an anti-creep laser melting flange chassis, which is the same as Example 1 and will not be repeated here. The difference is that in step S2, the Hf content is 0.08%; and in step S3, the oxygen content of the protective atmosphere is 40ppm.

[0096] Comparative Example 6: A method for preparing an anti-creep laser melting flange chassis, which is the same as Example 1 and will not be repeated here. The difference is that in step S2, the Hf content is 0.35%; and in step S3, the oxygen content of the protective atmosphere is 160ppm.

[0097] Comparative Example 7: A method for preparing an anti-creep laser melting flange chassis, which is the same as Example 1 and will not be repeated here. The difference is that in step S2, Nb is not added to the modified alloy powder (Nb content is 0%), and the balance is made up by Ni.

[0098] Comparative Example 8: A method for preparing an anti-creep laser melting flange chassis, which is the same as Example 1 and will not be repeated here. The difference is that in step S2, Nb is not added to the modified alloy powder, but is replaced by 3.0% rhenium (Re).

[0099] Comparative Example 9: A method for preparing an anti-creep laser melting flange chassis, which is the same as Example 1 and will not be repeated here. The difference is that in step S2, no Hf is added to the modified alloy powder (Hf content is 0%), and the balance is made up by Ni.

[0100] Comparative Example 10: A method for preparing an anti-creep laser melting flange chassis. The similarities with Example 1 will not be repeated here. The difference is that in step S3, conventional high-purity nitrogen is used for protection, and the oxygen content is controlled at <10ppm.

[0101] Comparative Example 11: A method for preparing an anti-creep laser melting flange chassis. The similarities with Example 1 will not be repeated here. The differences are: no Hf is added in step S2, and an oxygen-free atmosphere (oxygen <10ppm) is used in step S3. However, 0.5% Y2O3 nanoparticles are added to the alloy powder in step S2 by mechanical ball milling.

[0102] Experimental Example 1: Samples of Examples 1-5, Comparative Examples 1-4, and Comparative Examples 7-8 were selected to conduct tests on the obtained anti-creep laser melting flange chassis functional main body layer; Three parameters are obtained during the detection process: Steady-state creep rate at 1200℃ / 100MPa was obtained by using a high-temperature tensile creep testing machine to record strain-time curves under constant stress of 100MPa at 1200℃. The slope of the second stage, i.e. the steady-state period, was extracted and the unit is % / h.

[0103] The segregation coefficient of the strengthening element in the dendrite core is a dimensionless parameter. It is obtained by using an electron probe microanalyzer to perform a line scan on the cross-section of the functional host layer and taking the ratio of the peak concentration of the strengthening element in the dendrite core region to the nominal concentration.

[0104] The average equivalent size of the σ phase at grain boundaries was obtained by dark-field imaging of the precipitated phase at grain boundaries using transmission electron microscopy combined with energy dispersive spectroscopy, and the equivalent circle diameter of at least 50 σ phase particles was obtained by statistical analysis using image processing software. The unit is nm.

[0105] Table 1. Test parameters of reverse segregation and brittle phase transformation

[0106] As shown in Table 1, the technical solution of this invention has stringent boundary sensitivity and is irreplaceable. Comparative test results near the endpoints show that when the Nb content slightly decreases to 1.4%, the Nb segregation coefficient of the dendrite trunk is insufficient, failing to form enough NbC carbide pinning dislocations, resulting in an order-of-magnitude deterioration in the creep rate. When the Nb content slightly increases to 2.6%, the supersaturated Nb causes the grain boundary σ phase to exceed the nanoscale critical value, rapidly coarsening to 340 nm and degenerating into a brittle phase that tears the matrix. When the scanning speed slightly decreases to 650 mm / s, the cooling rate is insufficient to trigger solute retention, reverse segregation completely fails, the Nb segregation coefficient drops below 1, becoming negative segregation, leading to insufficient dendrite trunk strength, the formation of a brittle phase between dendrites, and a surge in the creep rate.

[0107] The results of the comparative tests for missing and replaced Nb showed that without any Nb addition, the dendrite trunk lost its reinforcing framework, and the high-chromium matrix precipitated coarse lamellar σ phases up to 580 nm in size without Nb synergy, leading to rapid creep fracture of the material at 1200℃. Comparative Example 8 used expensive Re to replace Nb. Although Re can reduce the creep rate to some extent, its low segregation coefficient prevented the formation of the strong Nb dendrite trunk framework found in this invention, resulting in overall performance inferior to this invention.

[0108] It should be noted that Comparative Example 8 in Table 1 only shows the single comparative result of simply replacing 2.0% Nb with 3.0% Re. Theoretically, by further optimizing the amount of Re added or adjusting the laser process parameters, the Re-containing alloy system may achieve creep resistance comparable to or even slightly better than that of Example 1 of this invention. However, the Re-containing alloy system faces two irreconcilable fundamental contradictions: to ensure structural stability and suppress the precipitation of harmful topologically close-packed phases, the addition of Re requires reducing the chromium content to below 12.0%, which may sacrifice the material's resistance to high-temperature oxidation and hot corrosion at 1200°C. High chromium content is the key basis for achieving the synergistic protection of the three-layer self-healing oxide film in this invention; the market price of Re is about 20 to 30 times that of Nb, and global rhenium resources are highly concentrated in specific regions. This invention achieves steady-state creep at 1200℃ / 100MPa by using reverse segregation engineering and defect transformation strategies, leveraging the synergistic effect of inexpensive conventional elements such as Nb, Si, and Hf, without adding Re, while maintaining a high chromium content to ensure ultra-high temperature oxidation resistance, which aligns with the value orientation of green manufacturing and long-term development.

[0109] Example 2: Examples 1, 6, 7 and Comparative Examples 5, 6, 9-11 were selected to test the influence of the transition layer and outer surface. Three parameters were obtained during the test.

[0110] The line density of microscopic thermal cracks in the deposited state was obtained using an optical microscope. After cutting and polishing the deposited sample along the construction direction, the lengths of all microcracks per unit area were counted under 500x magnification. The unit is mm / mm. 2 .

[0111] The volume fraction of the high-melting-point framework phase between dendrites was obtained by Rietveld full-spectrum fitting refinement using X-ray diffraction and combined with surface distribution statistics from scanning electron microscopy backscattered electron images, in units of .

[0112] The oxide film peeling rate after 100 hours of constant temperature oxidation at 1200℃ was obtained by using a thermogravimetric analyzer to record the mass change of the sample before and after being kept at 1200℃ in air for 100 hours. The mass loss percentage was calculated by weighing the peeled-off collection. The unit is 1.

[0113] Table 2. Stability test results of self-healing liquid film and oxide film

[0114] This experiment verified the sensitivity and irreplaceable nature of the self-healing fluid film synergistically constructed by trace amounts of Hf and O2. Test results near the endpoint showed that, within the parameter ranges of Examples 1, 6, and 7, the thermal crack density was suppressed to <3 mm / mm. 2Within the safety threshold; when the Hf content slightly decreases to 0.08% and the O2 content decreases to 40ppm, sufficient framework phase cannot be formed between dendrites, the surface tension of the liquid film is insufficient, and the hot crack density increases dramatically to 18.6mm / mm. 2 When the Hf and O2 contents are slightly excessive, the excess oxygen leads to inclusions, the excess Hf precipitates brittle primary phases, the crack density rebounds, and the oxide film peels off due to excessive growth stress.

[0115] The results of the comparative tests on missing and replaced samples show that, in Comparative Example 9, without any Hf addition, the interdendritic space completely lost its physical support framework, resulting in a surge in hot crack density and direct material failure. Comparative Example 10, using a conventional oxygen-free atmosphere, could not generate nano-composite oxides in situ to improve the surface tension of the liquid film, and could not form a Nb₂O₅-SiO₂ composite self-healing layer when operating at 1200℃, leading to an oxide film peeling rate as high as 22.6%. Comparative Example 11 attempted to replace the in-situ reaction of this invention with conventionally added Y₂O₃ nanoparticles. The results showed that the added particles severely agglomerated in the laser molten pool, not only failing to effectively pin the liquid film, but also maintaining a high crack density, instead becoming the initiation point for oxide film peeling. This fully demonstrates the non-obviousness and superior effect of this invention's synergistic use of specific trace elements and atmosphere for in-situ defect transformation.

[0116] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A method for preparing a creep-resistant laser melting flange base, characterized in that, include: S1. Prepare the flange base plate and perform pretreatment and construction of the initial thermodynamic field; S2. Prepare modified alloy powder, wherein the modified alloy powder is based on IN738LC alloy and contains niobium, silicon, hafnium and carbon elements; S3. Based on the established thermodynamic initial field, modified alloy powder is used to perform the first stage laser melting on the surface of the flange chassis substrate to induce in-situ chemical reaction in order to form a transition layer and precursor. S4. Based on the precursor, modified alloy powder is used to perform a second-stage laser melting of the flange chassis substrate, and an anti-creep main structure is constructed by inducing reverse segregation. S5. Post-process the flange chassis by transforming the brittle phase at the microscopic grain boundaries into a strengthening phase with dislocation pinning effect through multi-stage thermodynamic reconstruction to obtain the final product. In step S3, the first stage of laser melting is carried out in a protective atmosphere containing oxygen and nitrogen, wherein the oxygen volume fraction is 50~150ppm and the nitrogen gas volume fraction is 50~100ppm, so as to induce the in-situ generation of NbN nanoparticles and self-healing liquid film network. The reverse segregation control in step S4 involves enriching niobium, which has a positive segregation tendency, in the core of the primary dendrite trunk to form a niobium-reinforced dendrite trunk, and enriching silicon, which has a negative segregation tendency, in the interdendritic region. Silicon reacts with hafnium and niobium to generate high-melting-point silicides, thus forming silicon-reinforced interdendritic regions. The second stage of laser melting employs a spiral scanning superposition with 90° interlayer rotation, a laser volume energy density of 55~75 J / mm³, and a cooling rate of 10... 4 ~10 5 K / s, to trigger positive segregation of niobium with a segregation coefficient of 1.5~2.0 and negative segregation of silicon with a segregation coefficient of 0.5~0.7; In step S5, the post-processing includes sequential hot isostatic pressing, directional recrystallization, and two-stage aging. The hot isostatic pressing is used to close microscopic defects and promote the homogenization and diffusion of alloying elements. The directional recrystallization induces preferential grain growth along a specific direction by applying a directional dynamic temperature gradient flow field to reduce weak transverse grain boundaries. The two-stage aging process uses staged isothermal holding at different temperatures to respectively promote the transformation of the σ-brittle phase into a nanoscale grain boundary pinning phase and promote the spheroidization of the Laves phase into a dislocation pinning phase. The two-stage aging treatment includes: the first stage is held at 1120℃ for 4-6 hours to promote the transformation of the σ phase into a discontinuous nano-reinforced phase with a size of 50-200 nm; the second stage is held at 850℃ for 10-15 hours to promote the spheroidization of the Laves phase into a (Ni,Co,Hf)2(Nb,Si) type dislocation pinning phase. The modified alloy powder uses IN738LC high-temperature alloy as the matrix and adds niobium, silicon, hafnium and carbon elements; the chemical composition of the modified alloy powder ranges from 15.5% to 16.4% by mass, 8.0% to 9.0%, 2.5% to 3.5%, 3.0% to 4.0%, 4.5% to 5.2%, 2.4% to 3.7%, 3.0% to 4.0%, 1.5% to 2.5%, 0.3% to 0.6%, 0.1% to 0.3%, 0.12% to 0.18%, 0.01% to 0.02%, 0.02% to 0.08%, with the remainder being nickel matrix and unavoidable trace impurities.

2. The method for preparing an anti-creep laser melting flange base according to claim 1, characterized in that: The pretreatment in step S1 includes: placing the substrate in a controlled atmosphere heat treatment furnace for high-temperature solution treatment and then cooling it; using high-pressure airflow to sandblast the surface of the cooled substrate with alumina particles with a particle size of 50~100μm to roughen its surface; fixing the sandblasted substrate on a constant temperature heating platform and preheating it at 400~450℃ for 10-12h to construct a uniformly distributed thermodynamic initial field.

3. The method for preparing an anti-creep laser melting flange chassis according to claim 1, characterized in that: In step S2, the preparation of modified alloy powder includes: weighing raw materials according to chemical composition, melting them in an induction melting furnace at 1500~1600℃ and electromagnetically stirring to make the elements diffuse evenly; using high-pressure nitrogen to atomize the melt, forming spherical particles, and then sieving to obtain modified alloy powder with a particle size of 15μm~53μm.

4. The method for preparing an anti-creep laser melting flange chassis according to claim 1, characterized in that: In step S4, laser-induced reverse segregation is used to make the positive segregation degree of niobium greater than that of silicon, forming an NbC carbide strengthening phase in the dendrite trunk and a high-melting-point silicide strengthening phase between dendrites.

5. A creep-resistant laser-melted flange base, prepared according to any one of claims 1-4, characterized in that, include: Flange base plate; The transition layer is metallurgically bonded to the substrate surface. It contains NbN nanoparticles and has a self-healing liquid film network between the dendrites, which is jointly pinned by nanocomposite oxides and HfNb2. The functional main layer, stacked on the transition layer, has NbC carbides formed by the positive segregation of niobium to strengthen the dendrite trunk; and high-melting-point silicides formed by the negative segregation of silicon to strengthen the interdendritic structure. The niobium-strengthened dendrite trunk and the silicon-strengthened interdendritic structure together constitute the reverse segregation structure. The functional host layer has a discontinuous distribution of nano-σ-reinforcing phase and spherical (Ni,Co,Hf)2(Nb,Si) type Laves dislocation pinning phase at the grain boundaries; In high-temperature service environments, three oxide films are generated in situ on the outer surface of the functional main body layer. The oxide films, from the inside to the outside, are: an amorphous SiO2 inner oxide layer, a Cr2O3 main protective layer, and a Nb2O5-SiO2 composite self-healing layer.

Citation Information

Patent Citations

  • Silicide particle reinforced laser-clad high abrasion resistance nickel-base alloy powder and preparation method thereof

    CN102990060A

  • High-gamma'-content nickel-based high-temperature alloy powder for additive manufacturing, using method therefore and nickel-based high-temperature alloy component

    CN112921206A